2011
DOI: 10.1109/tase.2010.2102019
|View full text |Cite
|
Sign up to set email alerts
|

Design and Control of Paired Mobile Robots Working Across a Thin Plate With Application to Aircraft Manufacturing

Abstract: A pair of mobile robots acting on opposite sides of a thin plate is developed for a class of tasks where robots have to work together, carrying a pair of end-effectors and traversing across a plate surface. Using powerful magnets, the paired robots attract each other, support themselves against gravity, and generate traction force to move across the panel.First, the design concept of paired mobile robots is presented, followed by dynamic modeling and magnetic analysis. Conditions for preventing the robot from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…Nowadays, with the development of the robot industry, the mobility, collaboration, and adaptability of robots have become stronger, and the manufacturing industry, which is the main application scenario of industrial robots, has shown a trend towards intelligence [1]. As a large-scale manufacturing industry, many processes in the aviation industry currently rely on manual work by workers [2], and the following problems need to be resolved: the high labor intensity of workers leads to poor consistency, the limited working time leads to low efficiency, and the fatigue caused by long-term labor leads to low precision. To meet the requirements of long life, fast cycle, high precision and low cost of aircraft, industrial robots are urgently needed to replace workers' positions [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, with the development of the robot industry, the mobility, collaboration, and adaptability of robots have become stronger, and the manufacturing industry, which is the main application scenario of industrial robots, has shown a trend towards intelligence [1]. As a large-scale manufacturing industry, many processes in the aviation industry currently rely on manual work by workers [2], and the following problems need to be resolved: the high labor intensity of workers leads to poor consistency, the limited working time leads to low efficiency, and the fatigue caused by long-term labor leads to low precision. To meet the requirements of long life, fast cycle, high precision and low cost of aircraft, industrial robots are urgently needed to replace workers' positions [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, mobile robot becomes a target for several applications, such as security patrolling [1], manufacturing [2,3], and materials handling in the warehouse [4][5][6]. The security robots become one of the most important topics in the robotics filed.…”
Section: Introductionmentioning
confidence: 99%